Designing Islamic-Cultural Based High School Curriculum for Economics-Accounting Course - Aldiwanto Landali; Niswatin Niswatin; Tanti Taha Maya (International Journal of Religious and Cultural Studies, 2022)
The purpose of this research is to design monolithic curriculum for shariah economics-accounting through workshops or discussion as well as its implementation for high schools in Gorontalo. The research also aims to evaluate performance based on the implemented model. By employing mixed method, the research began with curriculum workshop of economics-accounting and followed by monolitihic model implementation in Pohuwato. Performance evaluation was then conducted to investigate the model contribution to improve students' understanding. The research concludes a curriculum model that can be applied in high school as a major concentrated course and local-laden course, that has been proven to elevate students' understanding in Islamic economics, business, accounting.